PENGELOLAAN JURNAL WARDAH FAKULTAS DAKWAH DAN KOMUNIKASI UIN RADEN FATAH - Syahir Syahir (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
This research entitled The Management of Wardah Journal of Dakwah and Communication Faculty State Islamic University Raden Fatah. The problem of this research is how do the management of Wardah Journal of Dakwah and Communication Faculty State Islamic University Raden Fatah? The research approach is qualitative descriptive and the research instruments are interview, observation and documentation. The data analyses are data reduction, data display, and verification. The result is not very good because 7 indicators on the low levels, 4 indicators are average and 2 are in good level